2022
DOI: 10.3390/a15100383
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Fuzzy Cognitive Maps for Feature Selection in Big Data Classification

Abstract: The features of a dataset play an important role in the construction of a machine learning model. Because big datasets often have a large number of features, they may contain features that are less relevant to the machine learning task, which makes the process more time-consuming and complex. In order to facilitate learning, it is always recommended to remove the less significant features. The process of eliminating the irrelevant features and finding an optimal feature set involves comprehensively searching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Sajal et al [ 57 ] provided a method based on KNN, SVM, and NB, with accuracies of 90.50%, 87.00%, and 81.00% for five levels of classification in tremor analysis. Furthermore, Haritha et al [ 58 ] obtained 76.20%, 86.71%, 91.83%, 82.90%, and 87.03% accuracy utilizing NB, DT, RF, MLP, and LR, respectively. Abayomi-Alli et al [ 59 ] demonstrated a Bidirectional Long Short-Term Memory (BiLSTM) for the UCI PD dataset, and their model achieved an accuracy of 82.86% with the original data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sajal et al [ 57 ] provided a method based on KNN, SVM, and NB, with accuracies of 90.50%, 87.00%, and 81.00% for five levels of classification in tremor analysis. Furthermore, Haritha et al [ 58 ] obtained 76.20%, 86.71%, 91.83%, 82.90%, and 87.03% accuracy utilizing NB, DT, RF, MLP, and LR, respectively. Abayomi-Alli et al [ 59 ] demonstrated a Bidirectional Long Short-Term Memory (BiLSTM) for the UCI PD dataset, and their model achieved an accuracy of 82.86% with the original data.…”
Section: Resultsmentioning
confidence: 99%
“… Comparison between the proposed model and the recent approaches [ 56 , 57 , 58 , 59 , 60 ] using the same standard PD dataset. …”
Section: Figurementioning
confidence: 99%
“…The final state vector, representing the final global solution, was derived by amalgamating the aforementioned partial outcomes. The parallel learning of the FCM is depicted in Figure 3, which was adopted from [60].…”
Section: Parallelization Of Fcmmentioning
confidence: 99%
“…partial outcomes. The parallel learning of the FCM is depicted in Figure 3, which was adopted from [60].…”
Section: Parallel Genetic Algorithm To Determine the Community Struct...mentioning
confidence: 99%